Translations tools and techniques - Sandoval Alas, Alejandra Enedina
This paper contains a summary of the process of translation and the meaning of each step which is the method that translators must take into account to get a guide of what to do, and develop in the best way possible of what translators must accomplish with the translation of a text. Steps like scoping out the text, researching, creating the draft, reviewing the translation, taking breaks, proofreading, and refining the translation wording are very important. Also, a mind map is included and the explanation of each step of the translation process. Besides that, a definition of translation is placed to have a meaning of it. Likewise, all the original documents and their translations are included. This shows how the different techniques like the literal translation, the borrowing, the calque, the transposition technique, the modulation, and the equivalence are very important in this process. Also, the process of translation, and the tools that supports the work of translators for example dictionaries, programs, webpages specialized in translations, image editions, etc. to fulfill the expectations and accomplishment of what translators use in their translations.